2016
DOI: 10.1186/s12935-016-0365-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of integrin β3, a binding partner of kallistatin, leads to reduced viability, invasion and proliferation in NCI-H446 cells

Abstract: BackgroundKallistatin is a serine proteinase inhibitor and heparin-binding protein. It is considered an endogenous angiogenic inhibitor. In addition, multiple studies demonstrated that kallistatin directly inhibits cancer cell growth. However, the molecular mechanisms underlying these effects remain unclear.MethodsPull-down, immunoprecipitation, and immunoblotting were used for binding experiments. To elucidate the mechanisms, integrin β3 knockdown (siRNA) or blockage (antibody treatment) on the cell surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Immunoprecipitation of the kallistatin complex with its binding protein(s) was conducted as previously described [ 12 ]. Whole-cell HUVEC lysates were pretreated with protein A-Sepharose beads for 1 h at 4°C with rotation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunoprecipitation of the kallistatin complex with its binding protein(s) was conducted as previously described [ 12 ]. Whole-cell HUVEC lysates were pretreated with protein A-Sepharose beads for 1 h at 4°C with rotation.…”
Section: Methodsmentioning
confidence: 99%
“…It was later shown to exert a variety of biological effects in response to pathological conditions such as abnormal blood pressure regulation, tumor formation, and inflammation [ 6 , 8 , 9 ]. Previous studies conducted by our research group demonstrated that adenovirus-mediated kallistatin gene delivery inhibited human colorectal cancer, hepatocellular carcinomas, and small cell lung cancer mainly through inhibition of angiogenesis [ 10 12 ]. The anti-angiogenic functions of kallistatin are associated with its structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HUVEC migration was investigated using a modified Transwell assay (Costar, NY, USA; pore size 8 μm, 3422) in 24-well plates [ 29 ]. Deer eTMSB10 at 50, 100, and 150 ng/ml in 700 μl culture medium containing 5% FBS was placed in the bottom reservoir of each chamber.…”
Section: Methodsmentioning
confidence: 99%